Two years of physically active mathematics lessons enhance cognitive function and gross motor skills in primary school children. (November 2022) - Magistro, Daniele; Cooper, Simon B.; Carlevaro, Fabio; Marchetti, Ilaria; Magno, Francesca; Bardaglio, Giulia; Musella, Giovanni
Abstract: Physically active lessons have been shown to enhance academic achievement. However, the effects on cognitive function and gross motor skill development remain unknown. The present study examined how the incorporation of physical activity bouts within Mathematics lessons affects cognitive function and gross motor skill development across 2 years in primary school children. Eighty-two children (6.6 ± 0.3 y) were allocated to an intervention (n = 36; completing 8 h/wk of physically active lessons) or control (n = 46) group. A battery of cognitive function tests was completed, alongside the TGMD-3 to assess gross motor skills. Physically active Mathematics lessons led to greater improvements across all measures of cognition, when compared to the control group (digit span forwards, p < 0.001, d = 1.5; digit span backwards, p = 0.017, d = 1.0; free word recall: p < 0.001, d = 1.3; selective visual attention: p < 0.001, d = 0.3; verbal fluency: p < 0.001, d = 0.9; arithmetic: p < 0.001, d = 1.8). Furthermore, the intervention group demonstrated greater improvements in overall score on the TGMD-3 ( p < 0.001, d = 1.7), as well as the locomotion ( p < 0.001, d = 1.1) and object control ( p < 0.001, d = 1.5) sub-scales. The physically active Mathematics lessons intervention appears to offer synergistic benefits in relation to cognitive and motor development, which are critical for optimal development in the early years. Highlights: Physically active maths lessons synergistically improved cognition and motor skills. Arithmetic ability was enhanced, the intervention may enhance academic achievement. Implementation of physically active lessons in the curriculum is thus recommended.